Epitope unmasking in vulvovaginal candidiasis is associated with hyphal growth and neutrophilic infiltration - Pericolini, Eva; Perito, Stefano; Castagnoli, Anna; Gabrielli, Elena; Mencacci, Antonella; Blasi, Elisabetta; Vecchiarelli, Anna; Wheeler, Robert T. (PloS one, 2018)
Vaginal candidiasis is a common disorder in women of childbearing age, caused primarily by the dimorphic fungus Candida albicans. Since C. albicans is a normal commensal of the vaginal mucosa, a long-standing question is how the fungus switches from being a harmless commensal to a virulent pathogen. Work with human subjects and in mouse disease models suggests that host inflammatory processes drive the onset of symptomatic infection. Fungal cell wall molecules can induce inflammation through activation of epithelial and immune receptors that trigger pro-inflammatory cytokines and chemokines, but pathogenic fungi can evade recognition by masking these molecules. Knowledge about which cell wall epitopes are available for immune recognition during human infection could implicate specific ligands and receptors in the symptoms of vaginal candidiasis. To address this important gap, we directly probed the surface of fungi present in fresh vaginal samples obtained both from women with symptomatic Candida vaginitis and from women that are colonized but asymptomatic. We find that the pro-inflammatory cell wall polysaccharide β-glucan is largely masked from immune recognition, especially on yeast. It is only exposed on a small percentage of hyphal cells, where it tends to co-localize with enhanced levels of chitin. Enhanced β-glucan availability is only found in symptomatic patients with strong neutrophil infiltration, implicating neutrophils as a possible driver of these cell wall changes. This is especially interesting because neutrophils were recently shown to be necessary and sufficient to provoke enhanced β-glucan exposure in C. albicans, accompanied by elevated immune responses. Taken together, our data suggest that the architecture of C. albicans cell wall can be altered by environmental stress during vaginal candidiasis.